Proteção social “desprotegida”?: a integralidade do SUAS na realidade miúda de municípios pequenos do Estado de São Paulo - Saraiva, Lucivaine Galan (2023)
The content of this dissertation is anchored in the discussion of comprehensiveness from the perspective of complementary social protection in the Unified Social Assistance System (SUAS), with a focus on the interprotection relationship in small municipalities 1. The guiding thread runs through two specific objectives: a) to understand integrality from the perspective of SUAS and its degrees of presence in the relationship between the levels of social protection, understanding the role of the state entity in implementing special social protection services, considering the diversity and socio-territorial particularities of the small-sized municipalities 1; b) to examine the expressions of the presence of special protection demands and the modes of operation between basic and special medium-complexity social protection from the perspective of the small-sized municipalities 1, from the territorial scope of FORTSUAS - Fernandópolis Region/SP. Based on dialectical-critical analysis, the Social Assistance Policy is recognized as a public policy of non-contributory social protection that guarantees social security, whose constitutional markers are associated with the field of Social Security, together with Health and Social Security, in the Federal Constitution (1988). The methodological itinerary is based on qualitative research, involving a bibliographical review, documentary research and field research, with the application of individual and collective interviews, in order to understand the concept of noncontributory social protection in the historical construction of the PNAS (2004) and integrality as the organizational axis of the SUAS. In this context, to understand the performance of decentralized state management in the region studied, as well as to examine the presence of expressions of rights violations and violence in the realities of operation of basic and special social protection of medium complexity in small municipalities. From the point of view of the perspectives analyzed, intersectoriality is discussed as an intrinsic category of the integrality of the SUAS, territorial dynamics in their confluence with territorialities and ruralities and the examination of the regionalization of special social protection in the context of small municipalities. Among the findings of this study, it can be said that, in the reality of small municipalities, the challenges are manifested by heterogeneities, discrepancies and similarities in the modes of operation between PSB and medium-complexity PSE and expressions of the presence of demands for special social protection, corroborating the necessary incorporation into the public scene of the expansion of social assistance services in the social direction of a universalizing public policy in the list of citizenship rights